Obscured by administrative data? Racial disparities in occupational injury - Sabbath, Erika L.; Boden, Leslie I.; Williams, Jessica AR; Hashimoto, Dean; Hopcia, Karen; Sorensen, Glorian (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'Underreporting of occupational injuries is well documented, but underreporting patterns may vary by worker characteristics, obscuring disparities. We tested for racial and ethnic differences in injury reporting patterns by comparing injuries reported via research survey and administrative injury database in the same group of healthcare workers in the US. ' ' METHODS ': 'We used data from a cohort of 1568 hospital patient-care workers who were asked via survey whether they had been injured at work during the year prior (self-reported injury; N=244). Using the hospital’s injury database, we determined whether the same workers had reported injuries to the hospital’s occupational health service during that year (administratively reported injury; N=126). We compared data sources to test for racial and ethnic differences in injury reporting practices. ' ' RESULTS ': 'In logistic regression models adjusted for demographic and occupational characteristics, black workers’ odds of injury as measured by self-report data were 1.91 [95% confidence interval (95% CI) 1.04–3.49] compared with white workers. The same black workers’ odds of injury as measured by administrative data were 1.22 (95% CI 0.54–2.77) compared with white workers. ' ' CONCLUSIONS ': 'The undercount of occupational injuries in administrative versus self-report data may be greater among black compared to white workers, leading to underestimates of racial disparities in workplace injury.
Keywords: administrative data; health disparity; health inequality; healthcare worker; injury data; minority worker; occupational health; occupational injury; race; racial disparity; workplace injury